O ensino do Sistema de Numeração Decimal nas séries iniciais do Ensino Fundamental: as relações com a aprendizagem do sistema posicional - Milan, Ivonildes dos Santos (2017)
On this research, we aim to reflect upon the teaching and learning of the Decimal Number System on the second grade of elementary School, more specifically to analyze the didactical conditions that allow the comprehension of what is hidden - the positional system. We used some of the contributions of Mathematics’ Didactics that defends the usage of didactical situations that raise, in students, the use of previous knowledge to select, organize, interpret information, and make decisions, in order to allow them to find different ways to build mathematical knowledge. Our methodology is inspired by Didactical Engineering, which comprehends the usage/elaboration of didactical situations that ensemble a meaningful learning board in the classroom. The didactical sequence, elaborated by Argentinian researchers from the Didactical Situations Theory, integrates an investigation project - developed in the city of Buenos Aires with second grade students – and has, as a starting point, the interaction with written numbers. We applied the didactical sequence twice to second grade students from the same elementary school, located in São Paulo. Our research has brought relevant contributions, such as: the way students relate, think and comprehend the positional value; promote successive approximations on the value of algorithms that represent the first grouping of ten basis; justify the efficiency of didactical sequences in mathematical learning; identify variables, in teaching and learning, that secure the process of both successive conceptualization to new knowledge and also variables present in the usual teaching which unfeasible the construction process of knowledge by students, and yet, confirms the potential of the group discussions to Mathematical learning